APLIKASI BERBAGAI ZAT ANTIOKSIDAN SEBAGAI PENGHAMBAT BROWNING MEDIA TANAM EKSPLAN JATI PUTIH (Gmelina arborea Roxb) SECARA IN-VITRO - Guntur, Gusmiaty; Restu, Muh; AR, Mutiah Ummusyahidah (Jurnal Eboni, 2019)
Browning is the most problem in plant tissue culture, both in growing media and explants. Browning is formed by oxidation process of phenolic compounds thatcan caused tissue death. The objective of this study were to analyze the effect of antioxidants addition against browning and to determine the best antioxidant toinhibited browning of Gmelina arborea explant growing media. The research was conducted by two steps, namely preparation of Murashige and Skoog (MS) media which are added 2,4-D growth regulators and addition of antioxidant PVP, ascorbic acid and activated charcoal. The results indicated that the addition ofantioxidants in the media were able to inhibit browning process of the media as well as in the explant. Moreover, the ascorbic acid performed better ability to inhibit browning process compared to the other antioxidants.